Kajian Yuridis Terhadap Pelaksanaan Lidik Dan Sidik Dalam Perkara Tindak Pidana Korupsi Oleh Kepolisian Daerah Sumatera Utara (Studi Kasus Di Polda Sumut) - Simanjuntak, Irpan Sinphordi; Kartika, Arie; Lubis, Anggreni Atmei (Universitas Medan Area, 2024)
Corruption is an act that not only harms state finances, but also the economy of society. The crime of corruption that often occurs is a national problem that must be handled seriously, sought to overcome through a balance of certainty and clear steps, involving all the potential that exists in society, especially the government and the parties responsible for law enforcement. This research method uses normative juridical. The data obtained is sourced from secondary data. The process of investigation and investigation in criminal acts of corruption begins with complaints from the public, NGOs (non-governmental organizations), and dumas (public complaints); then the Police analyze the case; then if a criminal act of corruption is found, the investigator will conduct a case title; then the investigator seeks and collects evidence; then the investigator determines the suspect; then the investigator prepares the case file; and the corruption case file is submitted to the prosecutor's office. The obstacles of the Police in tackling criminal acts of corruption are internal obstacles and external obstacles, as for the internal obstacles are budget problems, human resources, facilities and infrastructure, while the external obstacle is the lack of public understanding of anti-corruption culture.